Dynamics of Poverty and Its Alleviation Programs (Empirical Study of District Panel Data in Grobogan Regency): Dinamika Kemiskinan dan Program-Program Pengentasannya (Studi Empiris Data Panel Kecamatan di Kabupaten Grobogan) - Kurnia, Arifah; Hasmarinii, Maulidyah Indira (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the influence and effectiveness of government policies in poverty alleviation programs in Grobogan Regency. This study uses the panel data method using software eviews 8. The results can be concluded that partially the Village Fund and Non-Cash Food Assistance variables have a negative and significant effect on poverty, while the Smart Indonesia Program has a positive but not significant effect on poverty. The simultaneous influence of the Village Fund, Non-Cash Food Aid, Smart Indonesia Program variables can simultaneously explain the poverty variable by 87.18%. While the remaining 12.82% is explained by variations of other variables that are not included in the model. The results of this research that have been researched continue the previous research which is interesting to study. With this research, it is hoped that it can be used as a reference for similar research in the future and can be taken into consideration by the government in poverty alleviation programs in Grobogan Regency in the context of alleviating poverty in the region.